Serum IL-1β, sIL-2R, IL-6, IL-8 and TNF-α in schizophrenic patients, relation with symptomatology and responsiveness to risperidone treatment. Issue 3 (2001) - Erbağci, Ayşe Binnur; Herken, Hasan; Köylüoglu, Oya; Yilmaz, Necat; Tarakçioglu, Mehmet
Abstract : Activation of the inflammatory response system and varied levels of cytokines in acute schizophrenia have been suggested by recent studies. Psychopharmacologic agents can differentially effect cytokine production, which suggests that therapeutic function of neuroleptics may involve immunomodulation. The present study was carried out to examine: (i) serum concentrations of interleukin (IL)-1β, soluble interleukin-2 receptor (sIL-2R), IL-6, IL-8 and tumour necrosis factor (TNF)- α in schizophrenic patients; (ii) their relation with psychopathological assessment; and (iii) the relation of the initial cytokine levels with responsiveness to risperidone therapy. Thirty-four drug-free schizophrenic patients with acute exacerbation and 23 age- and gender-matched healthy controls were recruited for this study. Psychopathological assessments at admission and throughout risperidone treatment for 60 days were recorded. Serum cytokine concentrations were determined with chemilumunescence assays. According to our results, serum IL-1β, sIL-2R, IL-6, IL-8 and TNF-α concentrations adjusted for age, gender, body mass index and smoking were no different in patients with schizophrenia and controls and among subtypes of schizophrenia. However, the initial TNF-α concentrations had a significant effect on Brief Psychiatric Rating Scale and Scale Assessment of Positive Symptoms scores. The initial cytokine concentrations of the patients responsive to risperidone were not significantly different from those of non-responsive patients. The present study demonstrates that plasma levels of IL-1β, sIL-2R, IL-6, IL-8 and TNF-α adjusted for confounding factors are not altered in drug-free schizophrenic patients at acute exacerbation. We suggest that, if cytokine production is altered in schizophrenia, these alterations may not be detectable in systemic circulation. According to our results, the therapeutic effect of risperidone is not related to basal levels of the aforementioned cytokines. However, serum TNF-α may contribute to symptomatology in schizophrenia.